Prosedur Dispensing Kacamata Dengan Lensa Progresif Untuk Pasien Presbiopia Di Optik Jaya Padang - suryanta, Dolly iman (CV. ITTC INDONESIA, 2023)
This scientific paper discusses the procedures for dispensing glasses with progressive lenses for presbyopia patients at Optik Jaya Padang. This Study aims to determine: (1) How is the refractive examination procedure for presbyopia patients at Optik Jaya. (2) How is the Dispensing Procedure of Glasses with Progressive Lenses for Presbyopia Patients at Optik Jaya Padang. This research design uses descriptive qualitative methods. The population in this study was an Optisien Refractionist at Optik Jaya Padang during July 10-11, 2023. The sampling technique used total sampling technique. Data was collected through questionnaires and research instruments using Check List. The results of the study, respondents in Optik Jaya padang were 1 person, namely Refractionist Optisien. The results showed that 9 questions (100%) of respondents knew and understood the refractive examination procedures for presbyopia patients. 10 questions (88.5%) of respondents performed and knew the procedures of dispensing spectacles with progressive lenses for presbyopia patients and (11.5%) of respondents did not perform the procedure of dispensing spectacles with progressive lenses for presbyopia patients. Based on the results of this study, there are several suggestions, namely: (1) It is recommended to the RO to dispense glasses with progressive lenses in accordance with all dispensing procedures. (2) It is recommended to Optics, to always maintain quality in optics and maintain consumer confidence in optics. (3) It is recommended to researchers, make this research as a means of developing knowledge and research obtained during lectures and opening up broader insights into thinking, and being able to apply it in the workplace and in the midst of society.